(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
Football is the most popular sport in the world. It is played by millions of people around the globe, from the youngest children to the oldest people. Football clubs spend tens of millions of euros on the best players, football stars match the fame of the most famous actors and singers. The most interesting games attract millions of viewers in front of TV sets, and hundreds of thousands of fans in the stands. Against the background of Western European clubs, our native, Polish football looks so pale. Dilapidated stadiums, clumsy football players, regular elimination of Polish clubs in the pre-qualifiers of European cups. All this makes the level of Polish football different from the best European leagues. Nevertheless, we have someone who makes us famous all over Europe, football fans. I will deal with them in my master’s thesis. At a time when we have ski jumping fans, supposedly the best volleyball audience in the world and recently a faction of motorized Formula 1 fans, football fans are very negative. Riots at stadiums, rude behavior and ubiquitous aggression - this is how the fan community in Poland is presented in the media. Nevertheless, football fans form the most interesting group of fans in terms of psychological and sociological research, which is why, in my opinion, it is worth spending some time on them. Psychologists and sociologists try to bring us closer to the image of a fan, they try to explain the causes of aggression among the subculture of football fans. This is quite a problem that I also wanted to deal with in my work. The aim of the work is to show the forms and level of aggression of a football fan in Poland, including explaining where aggression in this social group comes from, showing fans’ norms and principles, presenting various types of aggression and the degree of their development among fans. For this purpose, the literature in the field of psychology and sociology was used and I conducted research in a group of thirty football fans. The Psychological Aggression Syndrome Inventory was used for the research.